2007
DOI: 10.1093/ejo/cjm089
|View full text |Cite
|
Sign up to set email alerts
|

Eighteen-month bracket survival rate: conventional versus self-etch adhesive

Abstract: The aim of this study was to evaluate, over an 18-month period, the clinical performance of a self-etch adhesive [Transbond Plus Self Etching Primer (SEP), 3M Unitek] compared with a conventional adhesive that employs the etch-and-rinse approach (Transbond XT, 3M Unitek). One operator, using the straight-wire technique, bonded 567 metallic brackets to the teeth of 30 patients (age range 12-18 years) in a way that patients acted as self-control. The brackets were bonded following the manufacturers' instructions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
37
0
5

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 27 publications
3
37
0
5
Order By: Relevance
“…Finally, there may be excessive occlusal forces during the initial stage of treatment. 8,11 Some authors have reported a failure rate of up to 82% during this time. 10 Other studies confirmed the efficacy of SEP systems during the first 6 months of treatment when compared with conventional systems.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Finally, there may be excessive occlusal forces during the initial stage of treatment. 8,11 Some authors have reported a failure rate of up to 82% during this time. 10 Other studies confirmed the efficacy of SEP systems during the first 6 months of treatment when compared with conventional systems.…”
Section: Resultsmentioning
confidence: 92%
“…13 Several authors conducted shorter studies to compare SEP and conventional systems, from 6 to 12 or 18 months. [8][9][10][11][12][13][14] Our follow-up lasted longer, from 36 to 48 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations